The contribution of hydrothermally altered ocean crust to the mantle halogen and noble gas cycles. (15th June 2016) - Chavrit, Déborah; Burgess, Ray; Sumino, Hirochika; Teagle, Damon A.H.; Droop, Giles; Shimizu, Aya; Ballentine, Chris J.
Abstract: Recent studies suggest that seawater-derived noble gases and halogens are recycled into the deep mantle by the subduction of oceanic crust. To understand the processes controlling the availability of halogens and noble gases for subduction, we determined the noble gas elemental and isotopic ratios and halogen (Cl, Br, I) concentrations in 28 igneous samples from the altered oceanic crust (AOC) from 5 ODP sites in the Eastern and Western Pacific Ocean. Crushing followed by heating experiments enabled determination of noble gases and halogens in fluid inclusions and mineral phases respectively. Except for He and Ar, Ne, Kr and Xe isotopic ratios were all air-like suggesting that primary MORB signatures have been completely overprinted by air and/or seawater interaction. In contrast, 3 He/ 4 He ratios obtained by crushing indicate that a mantle helium component is still preserved, and 40 Ar/ 36 Ar values are affected by radiogenic decay in the mineral phases. The 130 Xe/ 36 Ar and 84 Kr/ 36 Ar ratios are respectively up to 15 times and 5 times higher than those of seawater and the highest ratios are found in samples affected by low temperature alteration (shallower than 800–900 m sub-basement). We consider three possible processes: (i) adsorption onto the clays present in the samples; (ii) fluid inclusions with a marine pore fluid composition; and (iii) fractionation of seawater through phase separation caused by boiling. Ninety percent of the Cl, Br and I were released during the heating experiments, showing that halogens are dominantly held in mineral phases prior to subduction. I/Cl ratios vary by 4 orders of magnitude, from 3 × 10 −6 to 2 × 10 −2 . The mean Br/Cl ratio is 30% lower than in MORB and seawater. I/Cl ratios lower than MORB values are attributed to Cl-rich amphibole formation caused by hydrothermal alteration at depths greater than 800–900 m sub-basement together with different extents of I loss during low and high temperature alteration. At shallower depths, I/Cl ratios higher than MORB values can be explained by the addition of organic-rich sediments or the presence of organic detritus, both known to efficiently sequester I. Concentrations of 36 Ar of the pre-subducting materials are sufficient to account for the 36 Ar and composition of the mantle in the context of existing subduction-flux models. We find the Cl subduction flux of the oceanic crust to be about three times higher than the previous estimates and that sufficient Cl and Br can potentially be delivered by subduction over the last 3 Ga to account for mantle source compositions.